(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: In spite of recent advances in ophthalmology, the diagnosis and treatment of uveitis is still a challenge. Purpose: To assess ocular hemodynamics in patients with primary and recurrent posterior uveitis (focal and disseminated chorioretinitis) using ophthalmic rheography. Material and Methods: One hundred and eighteen patients (mean age ± standard deviation, 37.2 ± 1.5 years) with posterior uveitis were included in the study. The median duration of recurrent posterior uveitis was 2920 days (range, 1080 to 5110 days). The etiology of chorioretinitis was not established in all patients of the study. The age-matched control group was composed of 16 healthy volunteers (32 eyes). Patients and controls underwent ophthalmic rheography (ORG) with Reocom, the computerized rheography apparatus (Kharkiv, Ukraine). ORG included measurements of ocular pulse blood filling (expressed as RQ, ‰ rheographic coefficient) and vascular tone (expressed as alpha/T percentage index), and volumetric pulse blood filling rate (expressed as Ohm/s). Results: In primary focal and disseminated chorioretinitis, inflammation was characterized by increased ocular circulation, which was manifested by (a) 20% increased ocular pulse blood filling (both for unilateral and bilateral inflammation); (b) 1.4-times and twice, respectively, increased volumetric pulse blood filling rate and (c) 12.5% and 33.3%, respectively, increased vascular tone in large-caliber vessels and small-caliber vessels. Ocular hemodynamics was increased in patients with unilateral recurrent focal, bilateral recurrent focal and bilateral recurrent disseminated chorioretinitis in the period of recurrence; particularly, ocular pulse blood filling was 17% increased, and volumetric pulse blood filling rate, 1.6 times increased. In addition, vascular tone in large-caliber vessels was increased. The period of remission in patients with focal chorioretinitis was characterized by normal ocular pulse blood filling, whereas in those with recurrent disseminated chorioretinitis, by 20% decreased ocular pulse blood filling compared to the norm. Volumetric pulse blood filling rate in the period or remission was 1.4-1.5-times increased in patients with focal chorioretinitis, but not in those with disseminated chorioretinitis. Conclusion: Ocular pulse blood filling, volumetric pulse blood filling rate, and vascular tone in large-caliber and small-caliber vessels were increased in patients with primary posterior uveitis and those with recurrent posterior uveitis in the period of recurrence, both for unilateral and bilateral inflammation. In patients with recurrent posterior uveitis, the period of remission was characterized by a wide range of changes, from normal values to mild deficits, in ocular pulse blood filling, as well as increased vascular tone in vessels, which requires adequate anti-ischemic treatment in the period between recurrences.